A cross-national study on restaurant attributes between Korea and China. Issue 2 (3rd June 2019) - Cha, Seong-Soo; Park, Cheol; Wang, Xiaowu
Abstract : Purpose: IThis study aims to investigate the effects of the consumption motivations of restaurant customers on their perception of the importance of experiential and functional restaurant attributes. Design/methodology/approach: A total of 330 questionnaires were issued in China (168) and Korea (162). The resulting data were analyzed using SPSS 22.0 to verify the reliability and validity of the measured variables. Structural equation modeling was used to test the hypotheses of the study. Findings: The results showed that customers with hedonic consumption motivation were more sensitive to the experiential attributes than to the functional attributes of a restaurant. In addition, those customers with utilitarian consumption motivation were more influenced by functional attributes than by experiential attributes. However, these relationships differed between China and Korea. In China, the consumers' hedonic motivation had a stronger relationship with functional restaurant attributes, which reflects a culture that emphasizes pragmatism. Originality/value: This study analyzed the relationship between the motives to eat at a restaurant and the evaluation of restaurant attributes and how this differed between China and Korea, while suggesting practical implications.